Effects of fermented Ginger and Coleus amboinicus extracts on growth and immune response in broilers - Irda, Irzal; Sari, Devi Kumala; Rusdin, Muhammad Aldi Rizsyal (Politeknik Negeri Jember, 2025)
This study investigated the effects of fermented of ginger (Zingiber officinale) and Coleus amboinicus extracts administered via drinking water on broiler growth performance and immune response. A completely randomized design was employed with four treatments and five replications, totaling 100 broiler chicks divided into cages of five birds each. The treatments consisted of drinking water supplemented with ginger fermented extracts at concentrations of 0% (T0, control), 2% (T1), 4% (T2), and 6% (T3). Parameters measured included feed intake, body weight gain (BWG), feed conversion ratio (FCR), and relative weights of lymphoid organs (thymus, bursa of Fabricius, and spleen). The results showed that fermented extract supplementation significantly improved broiler performance. T1 had the highest BWG (1415.4±31.17g), while T3 showed the highest feed intake (2496.56±59.37g). The most efficient FCR was observed in T1 (1.75±0.045). In terms of immune response, T2 significantly increased spleen weight (0.15±0.02%) compared to the control (0.09±0.01%). Phytochemical analysis demonstrated that fermentation enhanced the bioactive content of the extract, increasing total phenols 20.64 ppm, flavonoids 163.08 ppm, and antioxidant activity 20.8% inhibition 5000. These findings suggest that administering 2% fermented extract via drinking water optimally improves broiler growth, while 4% enhances immune response. Fermented ginger and Coleus amboinicus extract show potential as natural feed additives and could serve as a sustainable alternative to antibiotics in poultry production.